RACIAL HOSTILITY IN RICHARD LA GRAVENESE'S MOVIE FREEDOM WRITERS (2007): A SOCIOLOGICAL APPROACH - SURIANA, SEPTI (2011)
The study is about the relation between environment and character building in Richard Lagravenese's movie entitled Freedom Writers. The major problem in this research is how the racial hostility is reflected In Richard Lagravenese's movie Freedom Writers. The objectives of the study are to describe the structural elements of the movie and to describe the racial hostility in Richard LaGravenese's movie Freedom Writer based on a sociological approach. The writer conducts the research by using qualitative method that use the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie subtitle Freedom Writers itself and the secondary data include several references books of Sociological Approach. The object of the research is the racial hostility in Richard Lagravanese's Freedom Writers. The outcome of the study shows the following conclusion. Firstly, based on the structural analysis, it is apparent that in this movie, Richard LaGravenese expresses his idea that there must be persons that have to be braved to remove racial hostility. Secondly, based on the sociological analysis it is evident that the movie was closely related to the contemporary phenomena in which people may forward their individual interests to discard of racial hostility.